Benefits of graftage - Butterfield, Earl Carver (My University, 1898)
Introduction: In this paper the term graftage is used in its more general sense and includes both budding and grafting. Although the practice has been looked upon by some as mysterious and by others as pernicious, yet it is gaining favor, and is now being widely employed as a means of propagating fruits.
Citation: Butterfield, Earl Carver. Benefits of graftage. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Graftage; Budding; Fruits; Theses; Manuscripts (documents)